American Art in Belgium. - Paleis voor Schone Kunsten Brussel (Brussel : Paleis voor Schone Kunsten, 1977)
Acconci, Vito Hannibal ; Albers, Josef ; Andre, Carl ; Arakawa, Shusaku ; Artschwager, Richard ; Baldessari, John ; Barry, Robert ; Beckley, Bill ; Bochner, Mel ; Byars, James Lee ; Calder, Alexandre ; Christo, Javacheff ; Clarke, John Clem ; De Andrea, John ; De Maria, Walter ; Dine, Jim ; Estes, Richard ; Fisher, Joël ; etc.
American Art in Belgium, Paleis voor Schone Kunsten, Brussel, 25.5. - 28.8.1977
boek